2007
DOI: 10.1387/ijdb.062216tt
|View full text |Cite
|
Sign up to set email alerts
|

Amniotic fluid induces rapid epithelialization in the experimentally ruptured fetal mouse palate - implications for fetal wound healing

Abstract: Cleft of the secondary palate is one of the most common congenital birth defects in humans. The primary cause of cleft palate formation is a failure of fusion of bilateral palatal shelves, but rupture of the once fused palate has also been suggested to take place in utero. The possibility of post-fusion rupture of the palate in humans has hardly been accepted, mainly because in all the cleft palate cases, the cleft palatal edge is always covered with intact epithelium. To verify whether the intrauterine enviro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
10
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 45 publications
3
10
0
Order By: Relevance
“…The presence of more than one growth factor is evident from the effect of heat‐ and acid‐treatment, which showed the presence of both stable and labile active molecules in this mixture. This is in agreement with previous studies indicating that the effects of AF on wound healing are due to the presence of many factors rather than a single component 16 …”
Section: Discussionsupporting
confidence: 94%
See 4 more Smart Citations
“…The presence of more than one growth factor is evident from the effect of heat‐ and acid‐treatment, which showed the presence of both stable and labile active molecules in this mixture. This is in agreement with previous studies indicating that the effects of AF on wound healing are due to the presence of many factors rather than a single component 16 …”
Section: Discussionsupporting
confidence: 94%
“…This is in agreement with previous studies indicating that the effects of AF on wound healing are due to the presence of many factors rather than a single component. 16 Previous studies have shown the presence of various known growth factors in AF, such as bFGF, PDGF, TGF-b, EGF, or IGF-I. [22][23][24][25] In our effort to clarify which of the above factors is responsible for the mitogenic action of AF we have used inhibitors against their transmembrane receptors, and our data showed that the factors mainly responsible for this stimulatory action are PDGF and most importantly bFGF.…”
Section: Discussionmentioning
confidence: 89%
See 3 more Smart Citations